Scanning Probe Microscopy Electrical and Electromechanical Phenomena at the Nanoscale - Kalinin, Sergei V.; Gruverman, Alexei (Springer New York : Imprint: Springer, 2007)
Scanning Probe Microscopy brings up to date a constantly growing knowledge base of electrical and electromechanical characterization at the nanoscale. This comprehensive, two-volume set presents practical and theoretical issues of advanced scanning probe microscopy (SPM) techniques ranging from fundamental physical studies to device characterization, failure analysis, and nanofabrication. Volume 1 focuses on the technical aspects of SPM methods ranging from scanning tunneling potentiometry to electrochemical SPM, and addresses the fundamental physical phenomena underlying the SPM imaging mechanism. Volume 2 concentrates on the practical aspects of SPM characterization of a wide range of materials, including semiconductors, ferroelectrics, dielectrics, polymers, carbon nanotubes, and biomolecules, as well as on SPM-based approaches to nanofabrication and nanolithography.